A new integrated approach to study the thermal and mechanical response of vessels subject to a safe blowdown process. (May 2018) - Leporini, Mariella; D'Alessandro, Valerio; Mancini, Edoardo; Terenzi, Alessandro; Marchetti, Barbara; Giacchetta, Giancarlo; Grifoni, Roberta Cocci
Abstract: The problems related to the blowdown of pressure vessels containing mixtures of hydrocarbons are well known amongst industries involved in plant design and hydrocarbons extraction. In this paper a new integrate approach to study the rapid two-phase depressurization (blowdown) of a vessel containing a mixture of hydrocarbons is presented. The method presented is based on a new mathematical model developed by some of the authors for the thermo-fluid dynamic characterization of the process (VBsim) and the finite element analysis for the mechanical simulations. Indeed, the pressure and thermal stress levels to which the vessel is exposed during the blowdown can present a number of consequences, such as cracks in the walls that have to be predicted by an accurate simulation of the blowdown process. In addition, from the economic point of view it is important to properly simulate the two-phase vessel blowdown to ensure the selection of the most cost-effective materials to conduct this operation in safe conditions. To demonstrate the effectiveness of the present approach, a vessel blowdown case from literature has been simulated and the most critical points in terms of thermal and mechanical stresses of the vessel wall have been identified. In addition, the FEM model build up can be used also for a complete Design of Experiments (DOE) analysis. Highlights: We investigated the thermal and mechanical response of vessels subject to a blowdown process in order to properly design it. We demonstrated the importance to integrate the thermo-fluid characterization of the depressurization with the FEM analysis. We presented an application of the model with the calculation of the stress and thermal levels induced on a vessel's wall. We developed a model suitable also for successive DOE analysis.